2022
DOI: 10.1155/2022/1933504
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effects of Modified Duhuo Jisheng Decoction Combined with Arthroscopic Surgery on Bone Metabolism, Oxidative Stress, and Serum TLR4 and TGF‐β1 in Patients with Knee Osteoarthritis

Abstract: Objective. To analyze the effects of modified Duhuo Jisheng Decoction combined with arthroscopic surgery on bone metabolism, oxidative stress, and serum TLR4 and TGF-β1 in patients with knee osteoarthritis (KOA). Methods. Prospectively select 82 patients with KOA from January 2020 to January 2022 in our hospital and divide them into the control group and observation group according to the random number table method, with 41 patients in each group. The control group was treated with arthroscopic surgery alone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[17] Currently, studies on the mechanisms related to KOA treatment in Chinese medicine mainly involve oxidative stress, inflammatory response, cell differentiation, proliferation, and apoptosis. [17][18][19][20][21] For instance, Coixenolide can decrease inflammatory response by increasing peripheral serum Foxp3 + CD4 + CD25 + Treg ratio, which in turn controls immunological function in collagen-induced arthritic mice. [18] Artemisinin, the active ingredient in Artemisia annua, was shown to have significant inhibitory effects on the expression of IL-1β, IL-6, and TNF-α in in vitro cellular assays, and could effectively inhibit IL-1β-induced inflammatory responses in rat osteoarthritis (OA) chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Currently, studies on the mechanisms related to KOA treatment in Chinese medicine mainly involve oxidative stress, inflammatory response, cell differentiation, proliferation, and apoptosis. [17][18][19][20][21] For instance, Coixenolide can decrease inflammatory response by increasing peripheral serum Foxp3 + CD4 + CD25 + Treg ratio, which in turn controls immunological function in collagen-induced arthritic mice. [18] Artemisinin, the active ingredient in Artemisia annua, was shown to have significant inhibitory effects on the expression of IL-1β, IL-6, and TNF-α in in vitro cellular assays, and could effectively inhibit IL-1β-induced inflammatory responses in rat osteoarthritis (OA) chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%